MODELING AND SIMULATION OF A SUSTAINABLE EXTENDED RANGE ENHANCED ELECTRIC VEHICLE - Moura da Silveira, Alexandre; Singer Capaverde, Betina; Balmant, Wellington; Ramírez Sapucaia, Ben-Hur; Leno Nascimento Rocha, Alef; Sardi Venter, Giuliana; Viriato Coelho Vargas, Jose (Revista de Engenharia Térmica, 2025)
The global demand for energy and the environmental impact study of fossil fuel consumption has gained worldwide attention due to its importance and is a topic of ongoing discussion among researchers and policymakers. Proposing an alternative and environmentally friendly energy source is therefore of utmost relevance in promoting sustainable mobility. This project proposes the development of a solution for a connection and charging control system for electric vehicle range extenders using sustainable hydrogen generation and the use of fuel cells. The system to be studied includes a 5kW PEMFC, powered by a sustainable aluminum-based hydrogen generator delivering 70A at 72V, and commonly, electric vehicle high voltage systems are designed above 300V and up to 900V, requiring a system that can accommodate charge transfer between the fuel cell and the electric vehicle. The innovation of this project lies in the absence of a “off the shelf” ready to use solution available on the market and the need for control over different requests and specific operating conditions. For the study, a demonstrator electric vehicle with a range extender system is under construction, where experimental data such as power, voltage and current will be collected to assist in the development of a Matlab Simulink model for simulating operation and determining control parameters. The model includes a closed-loop PID controller driving a boost-type DCDC converter to increase the voltage from 72V to 350V. Its sizing must cover the operating range of both the fuel cell (60V to 110V) and the vehicle (280V to 400V) simultaneously. Preliminary results of this model show a good level of conversion and stability for an output voltage range around 350V using a PI type controller, with convergence to the reference output voltage in less than 5 s.